On nth commutativity degree of some 3-Engel groups - Yahya, Zainab (2012)
This paper focuses on some 3-Engel groups. Suppose x and y are elements of a group G. The commutativity degree of a group is the probability that two elements in the group commute and is denoted by P(G). Meanwhile, the n th commutativity degree of a group G is the probability that for any pairs of x and y in G, xn and y commute. In this paper, the n th commutativity degree of some 3-Engel groups is determined